The Haematopoietically-expressed homeobox transcription factor: roles in development, physiology and disease - Jackson, Jacob T.; Nutt, Stephen L.; McCormack, Matthew P. (Frontiers in Immunology, 2023)
The Haematopoietically expressed homeobox transcription factor (Hhex) is a transcriptional repressor that is of fundamental importance across species, as evident by its evolutionary conservation spanning fish, amphibians, birds, mice and humans. Indeed, Hhex maintains its vital functions throughout the lifespan of the organism, beginning in the oocyte, through fundamental stages of embryogenesis in the foregut endoderm. The endodermal development driven by Hhex gives rise to endocrine organs such as the pancreas in a process which is likely linked to its role as a risk factor in diabetes and pancreatic disorders. Hhex is also required for the normal development of the bile duct and liver, the latter also importantly being the initial site of haematopoiesis. These haematopoietic origins are governed by Hhex, leading to its crucial later roles in definitive haematopoietic stem cell (HSC) self-renewal, lymphopoiesis and haematological malignancy. Hhex is also necessary for the developing forebrain and thyroid gland, with this reliance on Hhex evident in its role in endocrine disorders later in life including a potential role in Alzheimer’s disease. Thus, the roles of Hhex in embryological development throughout evolution appear to be linked to its later roles in a variety of disease processes.